2018
DOI: 10.1007/s00784-017-2327-4
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid as a local hemostasis method after dental extraction in patients on warfarin: a randomized controlled clinical study

Abstract: Thus, this measure of local hemostasis in topical form with gauze compression and irrigation was shown to be more effective in reducing the time to attain immediate hemostasis, and in preventing intermediate hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 34 publications
0
28
0
4
Order By: Relevance
“…We need to mention that, besides the fibrin, other agents used in the formulation may contribute to the haemostatic effect of our NFAH. Tranexamic acid is a procoagulant drug that has an antifibrinolytic action and has been successfully used to reduce blood loss in several types of surgery (Meng, Pan, Xiong, & Liu, ; Queiroz et al, ; Suh, Kyung, Han, Cheong, & Lee, ; Zilinsky et al, ). Indeed, it has been shown that the use of tranexamic acid and fibrinogen reduces blood loss and improves coagulation measurements in a porcine model of liver injury (Zentai et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…We need to mention that, besides the fibrin, other agents used in the formulation may contribute to the haemostatic effect of our NFAH. Tranexamic acid is a procoagulant drug that has an antifibrinolytic action and has been successfully used to reduce blood loss in several types of surgery (Meng, Pan, Xiong, & Liu, ; Queiroz et al, ; Suh, Kyung, Han, Cheong, & Lee, ; Zilinsky et al, ). Indeed, it has been shown that the use of tranexamic acid and fibrinogen reduces blood loss and improves coagulation measurements in a porcine model of liver injury (Zentai et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Tranexamic acid is a useful antifibrinolytic agent. A 5% solution may be applied topically with gauze over a wound for five minutes 28 or by rinsing in the mouth postoperatively for 2 min, four times daily. 29 Tranexamic acid 4.8% mouthwash can be compounded by pharmacies (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, studies investigating the local application of TXA for bleeding control have been carried out in the setting of elective total knee arthroplasty and dental surgery showing promising results. [ 34 35 36 ] However, there are no studies investigating the role of local TXA application in obtaining bleeding control in trauma patients. In the current study, using an animal model of severe liver injury, we could detect a decrease in bleeding in the cohort packed with TXA soaked gauze.…”
Section: Discussionmentioning
confidence: 99%